Impact of leadership style on millenial employees’ performance / Norazlina Mahat - Mahat, Norazlina (2015)
In today competitive scenario, organization needs effective leadership in order to achieve the organization goals. Indeed leadership is the process of influence between leaders and subordinates in terms of a leader behavior influencing of subordinates behavior to accomplish the organizational objectives. Therefore, the success of an organization in realization its goals and objectives rely on the leaders of the organization and their leadership styles. In fact a rapidly changing world of work, the retirement of Veteran Leaders and Baby Boomers has resulted Millennial to fill more positions in organization. Meaning that, more members of younger generations enter the workforce * and its imperative for employers to understand the factors that boost their performance in in organizations. Thus, this dissertation specifically targets millennial employees that have been in the workforce as the future of organization vitality is dependent on the ability of millennial employees effectively accomplishing the desired outcome. As for Millennial, they have differenjt expectations, a new mindset and very technology driven. The employees from millennial generational cohort will be a dominant factor in a few years, making it important that today's organization begin to understand on how to influence these young employees to be useful for future human resource practices in order to manage them effectively. Therefore, it is interesting to investigate the leadership styles and factors that will influence the millennial employees’ performance. Leadership styles play a vital role in order to ensure employee to give their best performance to the organizations.